Alendronate promotes bone formation by inhibiting protein prenylation in osteoblasts in rat tooth replantation model - Koichiro Komatsu; Akemi Shimada; Tatsuya Shibata; Satoshi Wada; Hisashi Ideno; Kazuhisa Nakashima; Norio Amizuka; Masaki Noda; Akira Nifuji (2013)
Bisphosphonates (BPs) are a major class of antiresorptive drug, and their molecular mechanisms of antiresorptive action have been extensively studied. Recent studies have suggested that BPs target bone-forming cells as well as bone-resorbing cells. We previously demonstrated that local application of a nitrogen-containing BP (N-BP), alendronate (ALN), for a short period of time increased bone tissue in a rat tooth replantation model. Here, we investigated cellular mechanisms of bone formation by ALN. Bone histomorphometry confirmed that bone formation was increased by local application of ALN. ALN increased proliferation of bone-forming cells residing on the bone surface, whereas it suppressed the number of tartrate-resistant acid phosphatase (TRAP)-positive osteoclasts in vivo. Moreover, ALN treatment induced more alkaline phosphatase-positive and osteocalcin-positive cells on the bone surface than PBS treatment. In vitro studies revealed that pulse treatment with ALN promoted osteocalcin expression. To track the target cells of N-BPs, we applied fluorescence-labeled ALN (F-ALN) in vivo and in vitro. F-ALN was taken into bone-forming cells both in vivo and in vitro. This intracellular uptake was inhibited by endocytosis inhibitors. Furthermore, the endocytosis inhibitor dansylcadaverine (DC) suppressed ALN-stimulated osteoblastic differentiation in vitro and it suppressed the increase in alkaline phosphatase-positive bone-forming cells and subsequent bone formation in vivo. DC also blocked the inhibition of Rap1A prenylation by ALN in the osteoblastic cells. These data suggest that local application of ALN promotes bone formation by stimulating proliferation and differentiation of bone-forming cells as well as inhibiting osteoclast function. These effects may occur through endocytic incorporation of ALN and subsequent inhibition of protein prenylation.